Evaluation of Qualitative Attributes of Wild Jamun [Syzygium cumini (L.) Skeels] Fruits with Emphasis on their Potential as Natural Food Colourants - Patil, Swarooprani; Netravati; Gorabal, Kirankumar; Yalleshkumar, H. S.; Naika, Mahantesha B. N. (International Journal of Economic Plants, 2026)
The experiment was conducted during October, 2024 to April, 2025 at the Department of Postharvest Management, KRCCH, Arabhavi, Belagavi, Karnataka to study the physical and biochemical characteristics of wild jamun fruits to assess their anthocyanin pigment for food applications. The fruits were examined for their physical dimensions, colour, and biochemical composition using standard analytical methods. The average fruit weight, length, width, and volume were 2.02 g, 1.68 cm, 1.28 cm, and 3.00 cm³, respectively, with a pulp-to-seed ratio of 1.40, indicating a seed-dominant structure. Colour measurements (L*=16.76, a*= 6.66, b*=-7.00) revealed a deep-purple hue characteristic of high anthocyanin content. The fruits exhibited total soluble solids of 14.4°Brix and titratable acidity of 0.67%, yielding a TSS/acid ratio of 21.5, suitable for fresh consumption. Biochemical analysis showed exceptionally high total monomeric anthocyanin content (1094.11 mg 100 g-1), ascorbic acid (166.2 mg 100 g-1), flavonoids (118.99 mg 100 g-1), total sugars (12.40%), and ash content (0.76%). Overall, the selected wild jamun was identified as a nutrient-rich, functionally valuable fruit with significant potential for utilization in food and nutraceutical applications. Specifically, for the application as natural food colorant, the jamun anthocyanin pigment can be utilized due to its deep-purple hue and high anthocyanin content. Despite its low pulp yield, the fruit’s seed fraction may be further explored for value-added products such as oil and protein recovery.